HUBUNGAN KETELADANAN KEPALA SEKOLAH DENGAN DISIPLIN KINERJA GURU DI SMP NEGERI SE-KECAMATAN BUNTA - ARMIN HALUTI; AKBAR SUDIRMAN (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2018)
The aim of the study was to find an objective and effective description of the relationship of the Headmasters Exemplary and Giving Reward toward work discipline of SMP Negeri teachers of Bunta District. This study was conducted in Bunta District with the beggining process was the implementation of testing instrument. The approach of this study was quantitative, and the types of this descriptive correlational, and it used statistical processing data. This study used simple correlation with one independent variable X and one dependent variabel Y. Then, it used moment product to search the correlation for X and Y. The sample measurement taken using probability sampling teachnique is simple random sampling. It expected that all population have opportunity to show the Headmaster exemplary had significant positive relationship or in the amount of 50,8% toward work discipline of SMP Negeri teachers in Bunta District. In other words, the better exemplary of headmaster, the better influence the exemplary relationship of headmaster, and the better work discipline of SMP Negeri teachers in Bunta District is giving reward or appreciation to the teachers or headmaster achievement.Suggestion: to obtain educational success, work discipline teachers should be improved through the exempalry of headmaster.